2009
DOI: 10.1038/jp.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid combined with ibuprofen in hypoxic ischemic encephalopathy: a randomized controlled trial

Abstract: Objective: Free oxygen radicals and proinflammatory cytokines are important causes for brain injury in neonates with hypoxic ischemic encephalopathy (HIE). Our objectives were to test the hypothesis that a combination of antioxidants (ascorbic acid) and anti-inflammatory agents (ibuprofen) can ameliorate the brain injury in HIE and improve neurodevelopmental outcomes when given to term infants immediately after birth.Study Design: In a prospective, randomized, double-blinded controlled trial, 60 asphyxiated te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Antioxidants have not been studied in drowning. One randomized trial found no benefit from ascorbic acid and ibuprofen in asphyxiated neonates [203]. There were no articles associated with CA.…”
Section: Post-hypoxic Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants have not been studied in drowning. One randomized trial found no benefit from ascorbic acid and ibuprofen in asphyxiated neonates [203]. There were no articles associated with CA.…”
Section: Post-hypoxic Pharmacologymentioning
confidence: 99%
“…2 LOE 5 studies showing benefit [205, 207], and 3 showing a neutral effect in CA or HIE [203, 206, 208]. …”
Section: Post-hypoxic Pharmacologymentioning
confidence: 99%
“…In human preterm neonates (<28 weeks gestation) indomethacin reduces white matter loss [137] although ibuprofen combined with ascorbic acid treatment in neonates reportedly has little effect on brain injury after severe HI [138]. Consistent with previous studies [86, 139142], we have shown that COX-2 is elevated in the brain after P3 HI and that ibuprofen significantly prevents this effect as well as P3 HI-induced increases in numbers of activated microglia, IL-1 β , and TNF- α levels [143].…”
Section: Role Of Neuroinflammation In Producing Neuronal Injurymentioning
confidence: 99%
“…111 Only one randomized-controlled clinical study in term infants who were asphyxiated has been performed, which found that the combination of AA with ibuprofen had no effect on outcome at 6 months of age. 112 …”
Section: Resultsmentioning
confidence: 99%